Genotype-phenotype correlations in patients with breast cancer and BRCA1 mutations (4153delA, 185delAG, 5382insC) - Ye. M. Bit-Sava; V. F. Semiglazov; Ye. N. Imyanitov (Опухоли женской репродуктивной системы)
Hereditary breast cancer (BC) associated with BRCA1 mutations is characterized by a number of features as compared to sporadic and BRCA2- associated BC. Structural and functional changes in mutant proteins in accordance with the type and locus of BRCA1 mutations determine different variants of a BC phenotype. Identification of genotype-phenotype correlations in patients with hereditary BC makes it possible to single out its basic characteristics, to personalize its diagnosis and treatment, to estimate the prognosis and risk of multiple primary tumors in accordance with BRCA1 mutations (4153delA, 185delAG, 5382insC).